SOFC管式欠氧催化自重整电极 (2019)
本发明涉及一种SOFC管式欠氧催化自重整电极，特点是包括气体密闭管、多孔蜂窝催化剂、电解质隔离层阴极层及阳极支撑电极管；阳极支撑电极管划分为三段工作区即从左至右依次为自重整工作区、电极反应工作区及尾气处理工作区；多孔蜂窝催化剂嵌入气体密闭管内，气体密闭管嵌入阳极支撑电极管的自重整工作区内，气体密闭管的长度与自重整工作区的长度相等；所述电解质隔离层阴极层套在阳极支撑电极管的电极反应工作区上，电解质隔离层阴极层的长度与电极反应工作区的长度相同。其将燃料重整与电极发电两大重要功能凝聚于电极管，最大程度减少管式SOFC燃料电池的制造成本、电池重量和体积。 The invention relates to a tubular oxygen-deficit catalytic self-reforming electrode for a SOFC. The tubular oxygen-deficit catalytic self-reforming electrode is characterized by comprising a gas enclosed pipe, a porous honeycomb catalyst, an electrolyte isolation layer cathode layer and an anode supporting electrode tube, wherein the anode supporting electrode tube is divided into three working zones, i.e., from left to right, a self-reforming working zone, an electrode reaction working zone and a tail gas treatment working zone; the porous honeycomb catalyst is embedded in the gas enclosed pipe; the gas enclosed pipe is embedded into the self-reforming working zone of the anode supporting electrode tube, and the length of the gas enclo